Implementasi Kepatuhan Syariah Pada Produk-Produk Pembiayaan di Bayt Al-Mal Surya Mandiri Cabang Pembantu Jetis - Khoiron, Hayyin Uhtiyani; Ulfah, Isnatin (Institut Agama Islam Negeri Ponorogo, 2022)
The Sharia Economic Law Compilation determines that the field of business to be carried out and the distribution of profits between the two parties must be stated clearly and definitely, as well as according to the agreement. In practice, mudarabah financing at BMT Surya Mandiri Capem Jetis only conducts surveys related to customer conditions without surveying the business fields carried out by customers, so the financing is sometimes used for consumptive needs. While profit sharing is considered less clear and definite, where profits should be shared, BMT only determines the percentage of profit itself without determining the percentage of profits that the customer as manager. In this study, the author looks at how KHES reviews the determination of business fields and profit sharing on financing products at BMT Surya Mandiri Sub Branch Jetis. From this research, it can be concluded that determination of business fields by KHES is financing provided to customers for business capital or increasing business capital. The financing is used for productive and profitable business fields. Meanwhile, the business fields not by the KHES are financing provided to meet the consumptive needs of customers, not for the business sector. The capital is used to meet personal needs that are not profitable. Furthermore, BMT only determines the percentage of its profit and includes the number of instalments and customer services each month without determining the percentage of profit that is part of the manager, so it is not by the provisions of KHES.